2022
DOI: 10.22144/ctu.jen.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-sowing seed treatments on rice yield, grain quality and soil chemical properties in salt-affected soils

Abstract: This study aimed to evaluate the effects of sowing density and iron (Fe) coated seeds on rice grain yield, grain quality, and soil properties in saline soils in Phuoc Long district, Bac Lieu province, Vietnam. Experimental treatments include: (T1) Intact dry seed (50 kg seed/ha); (T2) Hydro-primed seed (120 kg seed/ha); (T3) Hydro-primed seed (50 kg seed/ha); (T4) Hydro-primed then sprouted seed (50 kg seed/ha); (T5) Fe-coated dry seed (50 kg seed/ha); (T6) Fe-coated hydro-primed seed (120 kg seed/ha); (T7) Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Fe-coated primed dry rice seeds, a technology developed in 2004, and untreated rice seeds have both been sown onto paddy fields for comparison studies (Yamauchi, 2004). Some previous studies have shown that a change in the seed inoculation methods did not significantly affect the germination rate of rice seeds (Mori et al, 2012;Adhikari et al, 2013;Hao et al, 2016;Sarkar et al, 2019;Dung et al, 2021;Dung et al, 2022). Mori et al (2012) tested the germination rate of Fe-coated rice seeds under Vietnam Journal of Agricultural Sciences…”
Section: Rice Seed Germination Under Different Rice Seed Methodsmentioning
confidence: 99%
“…Fe-coated primed dry rice seeds, a technology developed in 2004, and untreated rice seeds have both been sown onto paddy fields for comparison studies (Yamauchi, 2004). Some previous studies have shown that a change in the seed inoculation methods did not significantly affect the germination rate of rice seeds (Mori et al, 2012;Adhikari et al, 2013;Hao et al, 2016;Sarkar et al, 2019;Dung et al, 2021;Dung et al, 2022). Mori et al (2012) tested the germination rate of Fe-coated rice seeds under Vietnam Journal of Agricultural Sciences…”
Section: Rice Seed Germination Under Different Rice Seed Methodsmentioning
confidence: 99%